Effects of latticeQCD EoS and continuous emission on some observables - Hama, Y.; Andrade, R.; Grassi, F.; Socolowski, O.; Kodama, T.; Tavares, B.; Padula, S. S. [UNESP] (My University, 2006)
Effects of lattice-QCD-inspired equations of state and continuous emission on some observables are discussed, by solving a 3D hydrodynamics. The particle multiplicity as well ν 2 are found to increase in the mid-rapidity. We also discuss the effects of the initial-condition fluctuations. © 2006 American Institute of Physics.
Keywords: Hydrodynamic model; LatticeQCD equations of state